The Hebrew word נזָיִר in Greek: from the Septuagint to the Christian authors - Lemardelé, Christophe (Semitica et Classica, 2015)
Abstract The Hebrew word nāzîr was problematic for the Septuagint translators. First translating it in accordance with the context of the Pentateuch, they later chose terms which mean “holy”, and eventually preferred transliterating it. As a consequence, readers of the Septuagint such as Philon, who did not know the Hebrew term, came to think that the Nazirite rite was a great vow of purity or even of purification according to the Greek text of Numbers 6. The Nazirite vow was entirely unknown to Christian authors, and their ignorance of the Hebrew word is the reason why Jesus, John the Baptist, and James the Just could not be thought of as nəzirîm like Samson. Abstract Le substantif hébraïque nāzîr a posé des problèmes aux traducteurs de la Septante. Ils l’ont d’abord traduit en fonction du contexte pour les livres du Pentateuque, puis ont choisi des termes du champ lexical de la sainteté avant d’opter pour la translittération. Ainsi, les lecteurs de la Bible en grec, comme Philon, n’avaient pas accès au terme en hébreu et pouvaient penser qu’il désignait un grand voeu de pureté, voire de purification selon le texte grec de Nombres 6. C’est pourquoi le rituel votif de nāzîr est resté obscur pour les auteurs chrétiens, c’est pourquoi encore leur ignorance du terme interdit de penser que Jésus, Jean le Baptiste et Jacques le Juste aient pu être des nəzirîm comme Samson.